Progress in the eradication of the feral cat (Felis catus) and recovery of the native fauna on Socorro Island, Revillagigedo Archipelago, Mexico - Ortiz-Alcaraz, Antonio; Aguirre-Muñoz, Alfonso; Arnaud-Franco, Gustavo; Galina-Tessaro, Patricia; Rojas-Mayoral, Evaristo; Méndez-Sánchez, Federico; Ortega-Rubio, Alfredo (THERYA, 2017)
Socorro Island, in the Revillagigedo Archipelago, has the highest number of endemisms of any Mexican island. It provides habitat for 117 vascular plants, 26 % of which are endemic to the island. Also endemic to the island are one reptile and eight terrestrial bird species. However, the local ecosystem has been heavily degraded by exotic mammals over the past 140 years. The feral sheep (Ovis aries) has contributed to a 30% loss in habitat based on the islandâ€™s surface area. Another serious threat is the feral cat (Felis catus), which has severely impacted the islandâ€™s bird communities and the endemic Socorro tree lizard (Urosaurus auriculatus). Together, feral sheep and cats are responsible for the extinction in the wild of the Socorro dove (Zenaida graysoni) and the Socorro Elf Owl (Micrathene whitneyi graysoni), and pose a serious threat for other vulnerable species, such as the Townsendâ€™s shearwater (Puffinus auricularis). The feral sheep was completely eradicated in 2012, which resulted in a rapid and remarkable recovery of the local vegetation cover. The eradication of the feral cat has been a complex issue to undertake due to the large size and topographical complexity of Socorro Island. In 2011 Grupo de Ecología y Conservacion de Islas, A. C. (GECI) started a feral cat control program, which scaled up into an eradication campaign. Here we report on the progress of the eradication campaign between 2011 and 2015, and provide a first assessment of the recovery of the native fauna. Beginning in 2011, camera traps were used to estimate cat abundance. Leg-hold and lethal traps were used to capture feral cats, some of them mounted with telemetry devices that alerted when traps were activated. Native vertebrates were monitored to confirm the positive effects derived from cat control efforts. By July 2015, 413 cats were dispatched using soft leg-hold and lethal traps, with a combined effort of 22,706 trap-nights. To date (mid-2016), cat abundance has decreased significantly, with cats being completely absent for several years in different areas of the island. The abundance of the endemic Socorro Island tree lizard and terrestrial birds has increased thanks to significant progress. Completing this important conservation action requires an increase in trapping efforts and the use of detection dogs, combined with night hunting. We estimate that the eradication of the feral cat will be completed by early 2017, after which the absence confirmation phase will begin.